Endovascular Management of a Subclavian Arterial Injury During Central Venous Catheter Placement for Hemodialysis - Ben Mrad, Imtinene (Open Access Emerg Med, 2021)
Subclavian artery injuries after central venous catheter placement constitute a rare but potentially fatal complication. The surgical repair of a subclavian artery trauma is a real challenge, associated with a high rate of morbidity and mortality. The role of endovascular treatment for vascular trauma, including injury to the subclavian artery, continues to evolve. In this manuscript, we report the case of an urgent endovascular repair by a covered stent graft of a subclavian artery perforation following the placement of a central venous catheter for dialysis in a 52-year-old patient, having a chronic kidney failure stage 5, with multiple comorbidities. The present case suggests that attention needs to be paid to preventing iatrogenic arterial cannulation during central vein catheterization to avoid potentially devastating complications. Endovascular treatment using a covered stent should be attempted as a first-line therapeutic option.